If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 9n + 11 = 65 Reorder the terms: 11 + 9n = 65 Solving 11 + 9n = 65 Solving for variable 'n'. Move all terms containing n to the left, all other terms to the right. Add '-11' to each side of the equation. 11 + -11 + 9n = 65 + -11 Combine like terms: 11 + -11 = 0 0 + 9n = 65 + -11 9n = 65 + -11 Combine like terms: 65 + -11 = 54 9n = 54 Divide each side by '9'. n = 6 Simplifying n = 6
| 2y+18+5y= | | 5x+10=8x | | 3x^4-4x^3+3=0 | | 7secx+7tanx=7 | | 5n-3+2n+6=3n+4-7n-9 | | 3(2x-6)=6(2x+1) | | 4+8=48 | | 6+6*6-6+6= | | f(x)=4x^2-1/9x^2-1 | | 6+6.6-6+6= | | 4=5/ | | x^2-12x+6=-30 | | 5x^2+20x+25=10 | | kx^2-(3k+1)x-15=0 | | kx^2+(3k-1)x-15=0 | | 5x^2-10x-70=5 | | =3-n | | =2n+1 | | 1/x-1/4=2/x | | x^2-2x-8=-7 | | 4x^2-8x-84=8 | | x^2+10x+12=3 | | =5n-20 | | 8m-15=9m+12 | | 1/4m-2m | | 4(x)-3=y | | 5(3-r)+2=3(r+2) | | -4x+21=3x | | -7x+4=2x-5 | | -8x-1=x+26 | | -4x-9=x+1 | | -3w+5=7w-3 |